Active control of nanodielectric-induced THz quasi-BIC in flexible metasurfaces : a platform for modulation and sensing - Tan, Thomas CaiWei (2021)
A bound state in the continuum (BIC) is a nonradiating state of light embedded in the continuum of propagating modes providing drastic enhancement of the electromagnetic field and its localization at micro–nanoscale. However, access to such modes in the far-field requires symmetry breaking. Here, it is demonstrated that a nanometric dielectric or semiconductor layer, 1000 times thinner than the resonant wavelength (λ/1000), induces a dynamically controllable quasi-bound state in the continuum (QBIC) with ultrahigh quality factor in a symmetric metallic metasurface at terahertz frequencies. Photoexcitation of nanostrips of germanium activates ultrafast switching of a QBIC resonance with 200% transmission intensity modulation and complete recovery within 7 ps on a low-loss flexible substrate. The nanostrips also form microchannels that provide an opportunity for BIC-based refractive index sensing. An optimization model is presented for (switchable) QBIC resonances of metamaterial arrays of planar symmetric resonators modified with any (active) dielectric for inverse metamaterial design that can serve as an enabling platform for active micro–nanophotonic devices.